Pengaruh Latihan Resistance Band Dan Zig-Zag Run Terhadap Tendangan Sabit Pada Siswa MTsN Kota Palopo - Andika Putra; Nur, Suaib; Jalil, Rasyidah (Jurnal Porkes, 2025)
The low speed of the scythe kick is a serious problem for students in the Tapak Suci MTsN Kota Palopo extracurricular program. Initial observations show that the majority of students are in the “very poor” category for scythe kick speed. This study aims to determine the effect and compare the effectiveness of resistance band training and zig-zag running on improving kicking speed. The method used is a quantitative experiment with a pretest-posttest two-group design. The sample consisted of 20 students who were purposively divided into two groups, each receiving different training treatments. The results of the study were significant in both groups. The resistance band group experienced an average increase from 13.50 to 21.90, while the zig-zag run group increased from 12.90 to 19.70. The paired sample t-test showed a significant effect of both exercises (sig. 0.000), but the independent sample t-test (sig. 0.83) showed no significant difference in effect between the two methods. The conclusion of this study is that both resistance band and zig-zag run exercises are equally effective in increasing the speed of the roundhouse kick, although resistance band exercises provide a higher average increase. A combination of both methods is highly recommended in training programs for optimal results.